The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2967/jnumed.117.200964
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Noninvasive Tracer Kinetic Analysis of 18F-Florbetaben PET Using a Dual–Time-Window Acquisition Protocol

Abstract: Accurate amyloid PET quantification is necessary for monitoring amyloid-β accumulation and response to therapy. Currently, most of the studies are analyzed using the static SUV ratio (SUVR) approach because of its simplicity. However, this approach may be influenced by changes in cerebral blood flow (CBF) or radiotracer clearance. Full tracer kinetic models require arterial blood sampling and dynamic image acquisition. The objectives of this work were, first, to validate a noninvasive kinetic modeling approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…The finding that DVR FLOW RLOGAN was robust against changes in CBF is in line with a previous study that found the same result for [ 11 C]PiB 5 and this robustness may be due to the linearity of the model. 24 In contrast, SRTM was found to be somewhat more sensitive to changes in CBF for both tracers, which is in agreement with work of Bullich et al 7 Their findings differ from the results reported here, in that they reported a slightly higher sensitivity of SRTM to cortical and a lower sensitivity to global CBF changes. This discrepancy may be attributed to differences in simulation design, the different cortical composite region and differences in fitter settings (such as parameter boundary values) between the studies.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The finding that DVR FLOW RLOGAN was robust against changes in CBF is in line with a previous study that found the same result for [ 11 C]PiB 5 and this robustness may be due to the linearity of the model. 24 In contrast, SRTM was found to be somewhat more sensitive to changes in CBF for both tracers, which is in agreement with work of Bullich et al 7 Their findings differ from the results reported here, in that they reported a slightly higher sensitivity of SRTM to cortical and a lower sensitivity to global CBF changes. This discrepancy may be attributed to differences in simulation design, the different cortical composite region and differences in fitter settings (such as parameter boundary values) between the studies.…”
Section: Discussionsupporting
confidence: 86%
“…This discrepancy may be attributed to differences in simulation design, the different cortical composite region and differences in fitter settings (such as parameter boundary values) between the studies. 7,22 In the present study, parameter boundary values were optimised to prevent fit parameters from becoming undetermined (i.e. k 2 and BP ND ), in particular for lower levels of amyloid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations